Fixed versus Removable Appliance for Palatal Expansion; A 3D Analysis Using the Finite Element Method. - Allahyar Geramy; Atefe Saffar Shahroudi (Tehran University of Medical Sciences, 2014)
Several appliances have been used for palatal expansion for treatment of posterior cross bite. The purpose of this study was to evaluate the stress induced in the apical and crestal alveolar bone and the pattern of tooth displacement following expansion via removable expansion plates or fixed-banded palatal expander using the finite element method (FEM) analysis.Two 3D FEM models were designed from a mesio-distal slice of the maxilla containing the upper first molars, their periodontium and alveolar bone. Two palatal expanders (removable and fixed) were modeled. The models were designed in SolidWorks 2006 and then transferred to ANSYS Workbench. The appliance halves were displaced 0.1 mm laterally. The von Mises stress in the apical, crestal, and PDL areas and also the vertical displacement of the cusps (palatal and buccal) was were evaluated.The total PDL stress was 0.40003 MPa in the removable appliance (RA) model and 4.88e-2 MPa in the fixed appliance (FA) model and the apical stress was 9.9e-2 and 1.17e-2 MPa, respectively. The crestal stress was 2.99e-1 MPa in RA and 7.62e-2 MPa in the FA. The stress in the cortical bone crest was 0.30327 and 7.9244e-2 MPa for RA and FA, respectively and 3.7271 and 7.4373e-2 MPa in crestal area of spongy bone, respectively. The vertical displacement of the buccal cusp and palatal cusp was 1.64e-2 and 5.90e-2 mm in RA and 1.05e-4 and 1.7e-4 mm in FA, respectively.The overall stress as well as apical and crestal stress in periodontium of anchor teeth was higher in RA than FA; RA elicited higher stress in both cortical and spongy bone. The vertical displacement of molar cusps was more in removable than fixed palatal expander model.